Analisis Peran Gaya Kepemimpinan Transformasional Kepala Sekolah dalam Meningkatkan Kinerja Guru: Studi Kasus di Sekolah Dasar - Garry Kurniawan; Lustani Samosir; Arip Surpi Samosir; Jans Pandapotan Siagian (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aims to examine how transformational leadership by school principals plays a role in improving teacher performance at the elementary school level. The research adopts a literature study approach, with data collected through documentation and analyzed using the Systematic Literature Review (SLR) method. The findings indicate that transformational leadership by school principals has a significant impact on enhancing teacher performance. Principals who are able to inspire and motivate teachers through a clear vision, emotional support, and by providing space for innovation can create a conducive work environment for professional teacher development. Furthermore, a leadership style that encourages collaboration and gives recognition for teachers’ achievements has been proven effective in boosting their work spirit and commitment to improving the quality of education. With such a leadership approach, principals are able to comprehensively enhance teacher performance, which ultimately has a positive impact on the quality of learning in elementary schools.